Decoding the Human Immunoglobulin G-Glycan Repertoire Reveals a Spectrum of Fc-Receptor- and Complement-Mediated-Effector Activities - Dekkers, Gillian; Treffers, Louise; Plomp, Rosina; Bentlage, Arthur E. H.; de Boer, Marcella; Koeleman, Carolien A. M.; Lissenberg-Thunnissen, Suzanne N.; Visser, Remco; Brouwer, Mieke; Mok, Juk Yee; Matlung, Hanke; van den Berg, Timo K.; et al. (Frontiers in Immunology, 2017)
Glycosylation of the immunoglobulin G (IgG)-Fc tail is required for binding to Fc-gamma receptors (FcγRs) and complement-component C1q. A variety of IgG1 glycoforms is detected in human sera. Several groups have found global or antigen specific skewing of IgG glycosylation, for example in autoimmune diseases, viral infections, and alloimmune reactions. The IgG glycoprofiles seem to correlate with disease outcome. Additionally, IgG-glycan composition contributes significantly to Ig based therapies, as for example IVIg in autoimmune diseases and therapeutic antibodies for cancer treatment. The effect of the different glycan modifications, especially of fucosylation, has been studied before. However the contribution of the 20 individual IgG glycoforms, in which the combined effect of all four modifications, to the IgG function has never been investigated. Here we combined six glyco-engineering methods to generate all 20 major human IgG1 glycoforms and screened their functional capacity for FcγR- and complement activity. Bisection had no effect on FcγR or C1q-binding, and sialylation had no- or little effect on FcγR-binding. We confirmed that hypo-fucosylation of IgG1 increased binding to FcγRIIIa and FcγRIIIb by ~17-fold, but in addition we showed that this effect could be further increased to ~40-fold for FcγRIIIa upon simultaneous hypo-fucosylation and hyper-galactosylation, resulting in enhanced NK-cell mediated antibody-dependent cellular-cytotoxicity (ADCC). Moreover, elevated galactosylation and sialylation significantly increased (independent of fucosylation) C1q-binding, downstream complement deposition, and cytotoxicity. In conclusion, fucosylation and galactosylation are primary mediators of functional changes in IgG for FcγR- and complement-mediated effector functions, respectively, with galactose having an auxiliary role for FcγRIII-mediated functions. This knowledge could be used for glycan profiling of clinically important (antigen-specific) IgG, but also to optimize therapeutic antibody applications.